175k views
2 votes
Please help me and show working. I have a test very soon.

Please help me and show working. I have a test very soon.-example-1
User Cornelb
by
6.1k points

1 Answer

5 votes

Answer:

c = 3

Explanation:

Given


(2)/(c-2) -
(3)/(c+2) =
(7)/(c^2-4) ← factor the difference of squares


(2)/(c-2) -
(3)/(c+2) =
(7)/((c-2)(c+2))

Multiply through by (c - 2)(c + 2) to clear the fractions

2(c + 2) - 3(c - 2) = 7 ← distribute and simplify left side

2c + 4 - 3c + 6 = 7

- c + 10 = 7 ( subtract 10 from both sides )

- c = - 3 ( multiply both sides by - 1 )

c = 3

User Rocky Singh
by
5.9k points